Proglacial river stage derived from georectified time-lapse camera images, Inglefield Land, Northwest Greenland - Goldstein, Seth N.; Ryan, Jonathan C.; How, Penelope R.; Esenther, Sarah E.; Pitcher, Lincoln H.; LeWinter, Adam L.; Overstreet, Brandon T.; Kyzivat, Ethan D.; Fayne, Jessica V.; Smith, Laurence C. (Frontiers in Earth Science, 2023)
The Greenland Ice Sheet is a leading source of global sea level rise, due to surface meltwater runoff and glacier calving. However, given a scarcity of proglacial river gauge measurements, ice sheet runoff remains poorly quantified. This lack of in situ observations is particularly acute in Northwest Greenland, a remote area releasing significant runoff and where traditional river gauging is exceptionally challenging. Here, we demonstrate that georectified time-lapse camera images accurately retrieve stage fluctuations of the proglacial Minturn River, Inglefield Land, over a three year study period. Camera images discern the river’s wetted shoreline position, and a terrestrial LiDAR scanner (TLS) scan of riverbank microtopography enables georectification of these positions to vertical estimates of river stage. This non-contact approach captures seasonal, diurnal, and episodic runoff draining a large (~2,800 km2) lobe of grounded ice at Inglefield Land with good accuracy relative to traditional in situ bubble-gauge measurements (r2=0.81, Root Mean Square Error (RMSE) ±0.185 m for image collection at 3-hour frequency; r2 = 0.92, RMSE ±0.109 m for resampled average daily frequency). Furthermore, camera images effectively supplement other instrument data gaps during icy and/or low flow conditions, which challenge bubble-gauges and other contact-based instruments. This benefit alone extends the effective seasonal hydrological monitoring period by ~2-4 weeks each year for the Minturn River. We conclude that low-cost, non-contact time-lapse camera methods offer good promise for monitoring proglacial meltwater runoff from the Greenland Ice Sheet and other harsh polar environments.